Diversity and composition of flowering plants in lahar-affected soils of La Salle Botanical Garden, Philippines - ALYANNA MARIE I. PARAS; ISABELLE BIANCA M. CASA; JAIME ZURI S. SAN LUIS; LUIS IÑIGO B. BRAVO; ALISSA JOLIE M. CO; DONN RODRIGO ISIDORE B. INCIONG; JUAN CARLO T. GUMANGAN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Paras AMI, Casa IBM, Luis JZSS, Bravo LIB, Co AJM, Inciong DRIB, Gumangan JCT. 2025. Diversity and composition of flowering plants in lahar-affected soils of La Salle Botanical Garden, Philippines. Biodiversitas 26: 6089-6098. The 1991 Mt. Pinatubo eruption and subsequent lahar flows created extensive sterile volcanic substrates that eliminated pre-existing vegetation, initiating primary succession across the landscape in Philippines. Despite extensive research on agricultural recovery efforts, natural vegetation recolonization patterns in these extreme environments remain poorly documented. This study conducted a rapid biodiversity assessment of flowering plants in lahar-affected soils at the La Salle Botanical Garden (LSBG) in Porac, Pampanga, Philippines, to characterize early successional dynamics and identify functional traits enabling establishment in volcanic substrates. Using the Line Intercept Technique across two temporal surveys (August-September 2024), eight angiosperm species from eight families were recorded, comprising three native and five naturalized taxa. The community exhibited low diversity (H' = 0.58) and strong dominance by two invasive species: Passiflora foetida and Asystasia gangetica, which collectively accounted for > 54.56% of relative density. While these pioneer species possess stress-tolerant traits—including drought tolerance, rapid growth, and efficient dispersal—that enable persistence in nutrient-poor, physically unstable lahar substrates, their dominance raises concerns about invasion-mediated alternative stable states that may prevent progression toward native-dominated communities. The overwhelming presence of invasive species suggests that natural succession alone is unlikely to restore native vegetation without active management intervention. Our findings provide critical baseline data for long-term monitoring and emphasize the urgent need for early invasive species control coupled with targeted enrichment planting of stress-tolerant native species to shift succession trajectories toward restoration goals. This study highlights LSBG's role as a living laboratory for understanding tropical volcanic succession and demonstrates how functional trait approaches can inform restoration practice in extreme disturbance environments.